2017
DOI: 10.1093/mnras/stx2919
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of supermassive Population III stars

Abstract: Supermassive primordial stars forming in atomically-cooled halos at z ∼ 15 − 20 are currently thought to be the progenitors of the earliest quasars in the Universe. In this picture, the star evolves under accretion rates of 0.1 -1 M yr −1 until the general relativistic instability triggers its collapse to a black hole at masses of ∼ 10 5 M . However, the ability of the accretion flow to sustain such high rates depends crucially on the photospheric properties of the accreting star, because its ionising radiatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
175
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(197 citation statements)
references
References 52 publications
12
175
0
Order By: Relevance
“…The analytic formula given by equation (9) still provides a good fit for the evolution of the stellar radius, though it only slightly overestimates the radius for M * 3 × 10 4 M . The similar evolution has been reported by the different authors (e.g., Umeda et al, 2016;Haemmerlé et al, 2018b). Figure 3 shows that a surface layer which only has a small fraction of the total mass significantly inflates to cover a large part of the stellar radial extent.…”
Section: Numerical Modeling Of Accreting Starssupporting
confidence: 87%
See 1 more Smart Citation
“…The analytic formula given by equation (9) still provides a good fit for the evolution of the stellar radius, though it only slightly overestimates the radius for M * 3 × 10 4 M . The similar evolution has been reported by the different authors (e.g., Umeda et al, 2016;Haemmerlé et al, 2018b). Figure 3 shows that a surface layer which only has a small fraction of the total mass significantly inflates to cover a large part of the stellar radial extent.…”
Section: Numerical Modeling Of Accreting Starssupporting
confidence: 87%
“…The limit in mass above which accreting SMSs become GR unstable has been investigated in numerical simulations (Umeda et al, 2016;Woods et al, 2017;Haemmerlé et al, 2018b), and are shown on Fig. 5.…”
Section: The Final Collapse Of Smssmentioning
confidence: 99%
“…The first and second vertical dark grey bands denote the transitions between stars which survive through core-helium burning and those which collapse at the end of core hydrogen-burning; and those which collapse at the end of core-hydrogen-burning and those which never undergo hydrostatic nuclear-burning, respectively. able, given that a significant portion of the mass in rapidlyaccreting models is in a high-entropy envelope, decoupled from the nuclear-burning convective core (Hosokawa et al 2013;Woods et al 2017;Haemmerlé et al 2018a). Second, there is no transition to truly direct collapses for even the highest accretion rates expected within the atomicallycooled halo scenario, or from a more agnostic standpoint, for infall rates up to 10 M ⊙ yr −1 .…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear at this point which of these two populations of SMS was more prevalent in the early universe because average LW background strengths are not well understood and supersonic streaming motions are thought to have produced about as many SMSs as LW backgrounds. Furthermore, it is not clear if these stars evolved along hot blue tracks or cool red ones, although there are indications that some would be blue (Haemmerlé et al 2018a). The prospects for detection of this second, less massive population of SMSs are unclear because it is not yet known if they were red or blue and they evolved in accretion envelopes with lower densities than those considered here.…”
Section: Radiation Hydrodynamical Calculations Bymentioning
confidence: 99%